Skopos in Advertising Translation into Arabic - Haddad, Khalil (2015)
A Master of Arts thesis in Translation and Interpreting MATI (English/Arabic/English) by Khalil Haddad entitled, "Skopos in Advertising Translation into Arabic," submitted in May 2015. Thesis advisor is Dr. Ahmed Ali. Soft and hard copy available.